src/Pure/deriv.ML
 changeset 1601 0ef6ea27ab15 parent 1593 69ed69a9c32a child 2042 33b4c1624e26
```--- a/src/Pure/deriv.ML	Thu Mar 21 11:13:05 1996 +0100
+++ b/src/Pure/deriv.ML	Thu Mar 21 13:02:26 1996 +0100
@@ -13,7 +13,7 @@
| Asm of int
| Res of deriv
| Equal of deriv
-		 | Thm   of theory * string
+		 | Thm   of string
| Other of deriv;

val size : deriv -> int
@@ -31,7 +31,7 @@
(*Conversion to linear format.  Children of a node are the LIST of inferences
justifying ONE of the premises*)
fun rev_deriv (Join (rl, [])) 	= [Join(rl,[])]
-  | rev_deriv (Join (Theorem arg, _)) 	= [Join(Theorem arg, [])]
+  | rev_deriv (Join (Theorem name, _)) 	= [Join(Theorem name, [])]
| rev_deriv (Join (Assumption arg, [der])) =
Join(Assumption arg,[]) :: rev_deriv der
| rev_deriv (Join (Bicompose arg, [rder, sder])) =
@@ -49,7 +49,7 @@
| Asm of int
| Res of deriv
| Equal of deriv
-               | Thm   of theory * string
+               | Thm   of string
| Other of deriv;

(*At position i, splice in value x, removing ngoal elements*)
@@ -64,7 +64,7 @@
simp_deriv der
| simp_deriv (Join (Equal_elim, [Join (Reflexive _, []), der])) =
simp_deriv der
-  | simp_deriv (Join (rule as Theorem arg, [_])) = Join (rule, [])
+  | simp_deriv (Join (rule as Theorem name, [_])) = Join (rule, [])
| simp_deriv (Join (rule, ders)) = Join (rule, map simp_deriv ders);

(*Proof term is an equality: first premise of equal_elim.
@@ -132,7 +132,7 @@
[rder, sder]), prfs) =
(*resolution with basic rule/assumption -- we hope!*)
tree_aux (sder, splice (i, Res (simp_deriv rder), ngoal, prfs))
-  | tree_aux (Join (Theorem arg, _), prfs)	= Join(Thm arg, prfs)
+  | tree_aux (Join (Theorem name, _), prfs)	= Join(Thm name, prfs)
| tree_aux (Join (_, [der]), prfs)	= tree_aux (der,prfs)
| tree_aux (der, prfs) = Join(Other (simp_deriv der), prfs);
```